Caution in cryptotephra correlation: resolving Lateglacial chemical controversies at Sluggan Bog, Northern Ireland. (17th June 2016) - MacLeod, A.; Davies, S. M.
ABSTRACT: Tephra layers are valuable stratigraphic and chronological markers in palaeoenviromental studies. Establishing robust linkages requires complete comparative databases of eruptive events to ensure that potential correlatives are not overlooked. This is achieved through the construction of tephrostratigraphical inventories from exposures proximal to the volcanic source. Proximally characterized ash layers are frequently detected thousands of kilometres from source alongside a limited number of tephras with no apparent proximal correlative. Despite the inability to correlate with a specific eruption, source volcanoes can be proposed and many of these far‐field occurrences have become well‐established stratigraphic markers. However, careful scrutiny is essential to verify the primary and instantaneous fallout origin of these distant occurrences. Here we present new data which provide an explanation for the long‐standing controversy surrounding the source of Lateglacial age cryptotephras within Sluggan Bog, Northern Ireland. Chemical analysis of glass shards detected within this sequence suggests they originate from an obsidian exposure located 11 km from the site, rather than from a contemporaneous eruptive event. This discovery highlights the importance of giving appropriate consideration to the enclosing geology of a particular palaeorecord. We suggest locations where geological sources might complicate air‐fall records of tephra deposition and propose a means by which to address this challenge.